Kinerja Peralatan Keamanan Bandara Adi Sutjipto Yogyakarta - Lolo Kustoro (Research and Development Agency of The Ministry of Transportation, 2012)
Oversight of security at an nirport for passengers, goods and vehicles should begin from the public men that everyone was free to go out without having to show identification cards (Pas airport), it is necessary to further the creation of safe situation for each passenger as well as anyone who activities in the airport region.Pengawasan keamanan di suatu bandar udara terhadap penumpang, barang dan kendaraan sebaiknya dimulai sejak dari area publik yang setiap orang masih bebas keluar masuk tanpa harus menunjukkan kartu pengenal (Pas bandar udara), hal ini diperlukan untuk lebih terciptanya situasi aman bagi setiap penumpang maupun siapapun yang melakukan kegiatan di wilayah bandar udara.